135 Combined radiofrequency and cryoablation for paroxysmal atrial fibrillation. A novel technique to reduce recurrences. (22nd September 2015) - Tayebjee, M H; Duncan, E; Baker, V; Dhinoja, M; Earley, M J; Sporton, S; Schilling, R J
Abstract : Introduction: We hypothesised that electrical isolation of the pulmonary veins (PV) by wide area circumferential ablation with radiofrequency (RFA) followed by selective PV ostial ablation using a cryoablation balloon (Cryo) would create parallel lines of block and reduce the incidence of PV reconnection.This would therefore improve first time success rates for paroxysmal atrial fibrillation (PAF). Methods: A retrospective study examined 59 consecutive patients undergoing first time PV isolation for symptomatic PAF(>1 year) and had failed at least two medical therapies. Patients received RFA alone, Cryo alone or combined RFA (to isolate PVs) followed by Cryo. Patients were followed up with 12 lead ECG, 7 day Holter monitoring and clinical review. Any atrial arrhythmia lasting greater than 30 s during a 3 month follow-up period was documented as a recurrence. Results: Significantly fewer patients had symptomatic palpitations (with documented PAF) in the combined group, with a trend towards need for less redo procedures (Abstract 135 table 1 ). Complications were one phrenic nerve palsy and one haematoma in the Cryo group, one grounding plate burn in the RF group and one phrenic nerve palsy, one pericardial effusion and one haematoma in the combined group. Total procedure time was greater in the combined group (Abstract 135 table 1 ). Conclusion: Preliminary results suggest that combination of RF and Cryoablation is superior to either alone. A prospective randomised trial is underway to confirm these findings.